1997
DOI: 10.1159/000169068
|View full text |Cite
|
Sign up to set email alerts
|

Successful Therapy of Tuberculosis in Hemodialysis Patients

Abstract: Tuberculosis associated with dialysis was studied at the Artificial Kidney Unit (AKU) in Abha, Saudi Arabia. There were 13 tuberculosis patients out of 270 patients on maintenance hemodialysis from August 1986 to July 1993, a prevalence of 4.8%. Ten (77%) were female and 3 (23%) were male, mean age of 51.23 ± 11.62 years. The main site of tuberculosis was pulmonary in 8 (62%) patients, in contrast to other studies. Mean duration on hemodialysis before diagnosis of tuberculosis was 19.23 ± 14.43 months and mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 14 publications
2
20
1
Order By: Relevance
“…However, the incidence of TB as shown by our study and others is considerably higher in dialysis patients than in the general population [2,8,9]. The inci- Al Shohaib/Scrimgeour/Shaerya dence of tuberculosis in this series was higher compared to previously published data [2,5,6], which were not from the Western Region (Jeddah). The Jeddah area is characterized by the presence of many immigrants.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…However, the incidence of TB as shown by our study and others is considerably higher in dialysis patients than in the general population [2,8,9]. The inci- Al Shohaib/Scrimgeour/Shaerya dence of tuberculosis in this series was higher compared to previously published data [2,5,6], which were not from the Western Region (Jeddah). The Jeddah area is characterized by the presence of many immigrants.…”
Section: Discussioncontrasting
confidence: 55%
“…These infections are acquired either before or after initiation of dialysis, and the latter may be via nosocomial modes of transmission [1]. Tuberculosis (TB) has been reported to be more common in the dialysis population compared to the general population [2]. The wide range of immunological derangements in chronic renal failure have been postulated to be the cause for the increased susceptibility of dialysis patients to tuberculosis [1].…”
Section: Introductionmentioning
confidence: 99%
“…In the study of PENNER et al [5], seven of 13 TB patients developed multiorgan failure and six of them died. However, other studies did not find a correlation between mortality and acute renal failure [2,9,26].…”
Section: Tuberculosis and Intensive Care R Erbes Et Almentioning
confidence: 88%
“…The details of the 10 cases examined by QFT-2G are listed in Table 5 Previous studies reported a high frequency of cases of TB discovered in the first year of dialysis (3,4,13,19 HD (HD >1 year) T a b l e 3 . Ra d i o l o g i c a l Cl a s s i f i c a t i o n o f 1 6 P a t i e n t s wi t h P u l mo n a r y T u b e r c u l o s i s …”
Section: Qft-2gmentioning
confidence: 99%
“…While some studies have reported a high mortality rate of 17-75% in uremic patients with TB (2,3), several have reported a very favorable outcome, with no mortality, which may be attributed to both an early diagnosis and treatment (4,5). However, making a diagnosis tends to be difficult and delayed since patients commonly present with extrapulmonary involvement and nonspecific symptoms mimicking uremia (6,7).…”
Section: Introductionmentioning
confidence: 99%